Expansion and Characterization of Neonatal Cardiac Pericytes Provides a Novel Cellular Option for Tissue Engineering in Congenital Heart Disease. Issue 6 (16th June 2015) - Avolio, Elisa; Rodriguez‐Arabaolaza, Iker; Spencer, Helen L.; Riu, Federica; Mangialardi, Giuseppe; Slater, Sadie C.; Rowlinson, Jonathan; Alvino, Valeria V.; Idowu, Oluwasomidotun O.; Soyombo, Stephanie; Oikawa, Atsuhiko; Swim, Megan M.; et al.
Abstract : Background: Living grafts produced by combining autologous heart‐resident stem/progenitor cells and tissue engineering could provide a new therapeutic option for definitive correction of congenital heart disease. The aim of the study was to investigate the antigenic profile, expansion/differentiation capacity, paracrine activity, and pro‐angiogenic potential of cardiac pericytes and to assess their engrafting capacity in clinically certified prosthetic grafts. Methods and Results: CD34 pos cells, negative for the endothelial markers CD31 and CD146, were identified by immunohistochemistry in cardiac leftovers from infants and children undergoing palliative repair of congenital cardiac defects. Following isolation by immunomagnetic bead‐sorting and culture on plastic in EGM‐2 medium supplemented with growth factors and serum, CD34 pos /CD31 neg cells gave rise to a clonogenic, highly proliferative (>20 million at P5), spindle‐shape cell population. The following populations were shown to expresses pericyte/mesenchymal and stemness markers. After exposure to differentiation media, the expanded cardiac pericytes acquired markers of vascular smooth muscle cells, but failed to differentiate into endothelial cells or cardiomyocytes. However, in Matrigel, cardiac pericytes form networks and enhance the network capacity of endothelial cells. Moreover, they produce collagen‐1 and release chemo‐attractants that stimulate the migration of c‐Kit pos cardiac stem cells. Cardiac pericytes were then seeded onto clinically approved xenograft scaffolds and cultured in a bioreactor. After 3 weeks, fluorescent microscopy showed that cardiac pericytes had penetrated into and colonized the graft. Conclusions: These findings open new avenues for cellular functionalization of prosthetic grafts to be applied in reconstructive surgery of congenital heart disease.